FILSAFAT KEADILAN DALAM HUKUM WARIS ISLAM - Faiz Faiz (Prodi Hukum Keluarga Fakultas Agama Islam Universitas Nurul Jadid, 2020)
the implementation of Islamic inheritance law begins with the death of a person or what is known in western civil law as ab intestine and does not recognize inheritance based on a will made by a living person which is known as testamentally inheritance. This principle is closely related to the principle of ijbari, that is, a person should not just decide the use of his property after his death. In Islam, a person can determine the use of his property after death through a will with certain limitations. Wasiat rules are separate from the rules of inheritance law in Islam, because in Islam justice is not only measured by the amount obtained when receiving inheritance rights, but also related to uses and needs or rights and obligations. Even the distribution of inheritance related to the amount can be done with the formua 1: 1 or as agreed. As long as the heirs give up and compromise if there is a part of them that must be released. If the heir maintains his rights, then he cannot be forced and he is given his right from the share of the inheritance